2009
DOI: 10.1073/pnas.0903090106
|View full text |Cite
|
Sign up to set email alerts
|

The preproghrelin gene is required for the normal integration of thermoregulation and sleep in mice

Abstract: Peptidergic mechanisms controlling feeding, metabolism, thermoregulation, and sleep overlap in the hypothalamus. Low ambient temperatures and food restriction induce hypothermic (torpor) bouts and characteristic metabolic and sleep changes in mice. We report that mice lacking the preproghrelin gene, but not those lacking the ghrelin receptor, have impaired abilities to manifest and integrate normal sleep and thermoregulatory responses to metabolic challenges. In response to fasting at 17°C (a subthermoneutral … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
42
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(51 citation statements)
references
References 40 publications
4
42
2
Order By: Relevance
“…However, these data are in contrast with other studies showing that, under extreme thermic conditions, both GHSR-KO (Szentirmai et al 2009) and GOAT-KO mice (Heppner et al 2013) can control core body temperature, and with those showing that AG administration does not alter body temperature in mice, rats, and humans (Wiedmer et al 2011). In this scenario, the actions of alternative ghrelin gene-derived peptides could shed some light on this controversy, in that, for example, obestatin has been shown to attenuate the hypothermic response of ghrelin gene KO mice (Szentirmai et al 2009), thereby suggesting a complex regulation of body temperature by the ghrelin system. Gastric motility and acid secretion AG is a potent accelerator of gastric emptying and a stimulator of GI motility in humans (Tack et al 2006), rats (Trudel et al 2002, and mice (Masuda et al 2000, Fujino et al 2003, Ariga et al 2007, Zheng et al 2009); while this effect was not observed in dogs (Ohno et al 2010).…”
Section: Nonendocrine Actionscontrasting
confidence: 55%
See 2 more Smart Citations
“…However, these data are in contrast with other studies showing that, under extreme thermic conditions, both GHSR-KO (Szentirmai et al 2009) and GOAT-KO mice (Heppner et al 2013) can control core body temperature, and with those showing that AG administration does not alter body temperature in mice, rats, and humans (Wiedmer et al 2011). In this scenario, the actions of alternative ghrelin gene-derived peptides could shed some light on this controversy, in that, for example, obestatin has been shown to attenuate the hypothermic response of ghrelin gene KO mice (Szentirmai et al 2009), thereby suggesting a complex regulation of body temperature by the ghrelin system. Gastric motility and acid secretion AG is a potent accelerator of gastric emptying and a stimulator of GI motility in humans (Tack et al 2006), rats (Trudel et al 2002, and mice (Masuda et al 2000, Fujino et al 2003, Ariga et al 2007, Zheng et al 2009); while this effect was not observed in dogs (Ohno et al 2010).…”
Section: Nonendocrine Actionscontrasting
confidence: 55%
“…This idea is supported by the fact that ghrelin gene KO mice cannot control body temperature under extreme thermic conditions (Szentirmai et al 2009), and because areas of the hypothalamus located in the vicinity of cold-sensitive neurons exhibit ghrelin-binding sites (Wiedmer et al 2011). However, these data are in contrast with other studies showing that, under extreme thermic conditions, both GHSR-KO (Szentirmai et al 2009) and GOAT-KO mice (Heppner et al 2013) can control core body temperature, and with those showing that AG administration does not alter body temperature in mice, rats, and humans (Wiedmer et al 2011). In this scenario, the actions of alternative ghrelin gene-derived peptides could shed some light on this controversy, in that, for example, obestatin has been shown to attenuate the hypothermic response of ghrelin gene KO mice (Szentirmai et al 2009), thereby suggesting a complex regulation of body temperature by the ghrelin system.…”
Section: Nonendocrine Actionsmentioning
confidence: 55%
See 1 more Smart Citation
“…Prior to treatment with obestatin, which is like a preproghrelin gene product, attenuated this hypothermic response of the preproghrelin knockout mice (Szentirmai et al, 2009) Previous studies suggest the occurrence of peaks of ghrelin around sleep onset (Cummings et al, 2001;Dzaja et al, 2004). This issue was not supported in a study with a more frequent sampling of blood specimens .…”
Section: -Please Insert Figure 5 Near To Here -mentioning
confidence: 99%
“…In according to a sleep-promoting effect of ghrelin, knockout mice for ghrelin had impaired physiologic sleep regulation and thermoregulatory responses too. Thus, in response to fasting at 17 °C, these knockout mice presented hypothermic bousts associated with a reduced sleep (Szentirmai et al, 2009). Furthermore, also previous studies in humans suggested a sleep-promoting effect of ghrelin, with the evidence of its peaks around the sleep onset (Dzaja et al, 2004).…”
Section: Ghrelin Regulation and Functionsmentioning
confidence: 99%